2021
DOI: 10.3390/foods10061165
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Nigerian Butchers’ Knowledge and Perception of Good Hygiene and Storage Practices: A Cattle Slaughterhouse Case Analysis

Abstract: In Nigeria, the National Agency for Food and Drug Administration and Control (NAFDAC) guides the inspection and production of beef meat and prescribes the good practices pertinent to beef products’ handling, processing, and packaging. Specifically, good hygiene practice (GHP) assures beef product safety and consumer protection, whereas good storage practice (GSP) assures the continuity of hygiene activities within the storage stages. Relevant literature about butchers’ knowledge and perception of good hygiene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…To determine food hygiene level of different food establishments, examine managers' opinion, and justify food hygiene importance via consumers' perception of food safety/hygiene practices at three European cities Okpala, Nwobi, and Korzeniowska [112] GHP (with GSP) Meat industry in Nsukka, Enugu State of Nigeria…”
Section: Food Production Plants Within Some Provinces In Polandmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine food hygiene level of different food establishments, examine managers' opinion, and justify food hygiene importance via consumers' perception of food safety/hygiene practices at three European cities Okpala, Nwobi, and Korzeniowska [112] GHP (with GSP) Meat industry in Nsukka, Enugu State of Nigeria…”
Section: Food Production Plants Within Some Provinces In Polandmentioning
confidence: 99%
“…[166] GHP alone or combined with GCP, GSP, HACCP, etc. investigated food handlers, [108,110,114,115] specifics like meat handlers, [105,107,112] different food (service) establishments, [111] like retail (meat) shops, [109] food truck, [103] food vendors, [106] urban street food sellers [113] and foodservice facilities [104] with variable outcomes . Ifeadike et al [110] assessed the food hygiene practice of food handlers in the FCT Nigeria, and found that majority washed their hands after using the toilets and underwent regular medical checkups, with much less (food handlers) either using disinfectants and sanitizers or checked the food temperature with a thermometer at the workplace.…”
Section: Good Hygiene Practice (Ghp)mentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, achieving high-level beef/meat quality from any given cattle slaughterhouse requires that optimum levels of good practices must be upheld. Regardless of location, cattle pre-slaughter and slaughter operations remain very critical to meat quality and food security [1][2][3]. There are pre-and post-slaughter conditions/factors in slaughterhouses that influence meat quality and food security.…”
Section: Introductionmentioning
confidence: 99%